Using Job-Shop Scheduling Tasks for Evaluating Collocated Communication - Tan, Desney; Gergle, Darren; Mandryk, Regan; Inkpen, Kori; Kellar, Melanie; Hawkey, Kirstie; Czerwinski, Mary (Journal of Personal and Ubiquitous Computing (Special Issue on User-Centered Design and Evaluation of Services for Human-Human Communication and Collaboration), 2007)
Researchers have begun to explore tools that allow multiple users to collaborate across multiple devices in collocated environments. These tools often allow users to simultaneously place and interact with information on shared displays. Unfortunately, there is a lack of experimental tasks to evaluate the effectiveness of these tools for information coordination in such scenarios. In this article, we introduce job-shop scheduling as a task that could be used to evaluate systems and interactions within computer supported collaboration environments. We describe properties that make the task useful, as well as evaluation measures that may be used. We also present two experiments as case studies to illustrate the breadth of scenarios in which this task may be applied. The first experiment shows the differences when users interact with different communicative gesturing schemes, while the second demonstrates the benefits of shared visual information on large displays. We close by discussing the general applicability of the tasks.